Convergence of Global Solutions to the Cauchy Problem for the Replicator Equation in Spatial Economics - Minoru Tabata; Nobuoki Eshima (Discrete Dynamics in Nature and Society)
We study the initial-value problem for the replicator equation of the N-region Core-Periphery model in spatial economics. The main result shows that if workers are sufficiently agglomerated in a region at the initial time, then the initial-value problem has a unique global solution that converges to the equilibrium solution expressed by full agglomeration in that region.